Penerapan e-Planning di Kota Palembang - Ermadiani Ermadiani; Ubaidillah Ubaidillah; Abdulrohman Abdulrohman (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
To create Good Governance, local government innovation is really needed. In this case, the innovation of regional development planning becomes technology-based. The government of Palembang City is one of the local governments in Indonesia that innovates to create Good Governance. This information technology-based local development planning process is called as e-Planning. This study used a qualitative descriptive analysis method. The data used was primary data obtained through interviews. The results of the study explained that e-Planning is a regional innovation in Local Government Governance. The technology adoption used in e-Planning in Palembang City is Cyber Government or what is often known as e-Government. The e-Planning process in the city of Palembang is in accordance with the timeline or schedule sourced from Bapped Litbang Kota Palembang. Implementing e-Planning at the Government of Palembang City is considered to be better, more effective, more efficient, more complete, more accurate, and easier than before its implementation. It is just that the synchronization and integration between SIMDA Finance and SIPD of the Ministry of Internal Affairs, between e-Planning and e-Budgeting are still not optimal, so as a form of the Palembang City Government's commitment to create Good Governance is required upgrading, repairing, refinement and system maintenance.